On the Teaching of Poetry in English Journal, 1912-2005: Does History Matter?. (March 2014) - Dressman, Mark; Faust, Mark
This study reports two stages of research into the discourses of poetry education in the United States from the early 20th to the early 21st centuries. The first is an original study that traces the history of discourses about teaching poetry, and the second is a coda or concluding analysis that raises questions about how history functions as a trope and whether or how the history of poetry education matters in the present. In the original study, we photocopied, inventoried, coded, and noted patterns of discourse over virtually every article published on the teaching of poetry in the oldest practice-oriented journal of literacy education in the United States, English Journal, from 1912 to 2005. In the coda that follows, we revisited and refined conclusions from our initial round of investigation in light of the theoretical implications of three models of historical and social change: Parsonian functionalist theories, Marxist/neo-Marxist theories of dialectical materialism, and Foucauldian theories of discourse, power, and practice. In conclusion, we consider the implications of history and of historical thinking for present and future research and practice.